2001
DOI: 10.1111/1467-6494.00138
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Strength of Personal Constructs Versus Conventional Constructs: Self‐Image Disparity and Neuroticism

Abstract: Idiographic personal construct (PC) measures of self-image disparity were hypothesized to be stronger than nonidiographic conventional construct (CC) measures in predicting neuroticism. Ninety-six college students completed PC and CC measures of real self, ideal self, social self, and ideal social self; the NEO Five-Factor Inventory; and the Marlowe-Crowne Social Desirability Scale. Content analysis showed that individuals' PC measures were unique. The disparity between real self and ideal self and the dispari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 55 publications
2
27
1
1
Order By: Relevance
“…One study used the CICA measure and found actual-ideal discrepancies were related to a range of psychological symptoms (Renner & Leibetseder, 2000). Morretti and Higgins (1990) found that idiographic measures of ideal-ought discrepancies related to measures of self-esteem in students, and Watson and Watts (2001) found that when using idiographic measures self-discrepancies related to higher levels of neuroticism in a non-clinical sample.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One study used the CICA measure and found actual-ideal discrepancies were related to a range of psychological symptoms (Renner & Leibetseder, 2000). Morretti and Higgins (1990) found that idiographic measures of ideal-ought discrepancies related to measures of self-esteem in students, and Watson and Watts (2001) found that when using idiographic measures self-discrepancies related to higher levels of neuroticism in a non-clinical sample.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…could not be calculated from reported data). Morretti and Higgins (1990) Students; cross-sectional 60 Ideal-ought discrepancy (idiographic -self nominated attributes, and nomotheticpersonality characteristics) SES Idiographic ideal-ought discrepancy was negatively related to self-esteem (r = À.55), nomothetic real-ideal discrepancies were associated with self-esteem (r = À.34) Renner and Leibetseder (2000) Psychotherapy patients and controls; cross-sectional 139 Dyadic conflict (inconsistency between attitudes and reality) (Lauterbach Computerised Intrapersonal Conflict Assessment (CICA)) GSI SCL Positive associations were found between dyadic conflict and all clinical symptom measures in the combined sample, low conflict group and high conflict group (combined group r = .62 depression, .53 anxiety) Watson and Watts (2001) Students; cross-sectional 96 Personal construct (idiographic) and conventional construct measures of actual-ideal discrepancy and discrepancy between actual and ideal social selves Neuroticism (NEO-FFI) Real-ideal discrepancies related to neuroticism (r = .52) Berking et al (2003) Psychotherapy in-patients; prospective (end of therapy follow up, mean time 39 days or 7 sessions) 62 Incongruence questionnaire (INK) VEV (changes in behaviour and experience), therapy outcome Incongruence was reduced in CBT; the reduction in incongruence was associated with the positive change in outcome measures (r = .50 for improvement in wellbeing) 2d. Self-concordance and success in personal goals…”
Section: Hopelessness Bdi Suicidal Ideationmentioning
confidence: 99%
“…In fact, several studies indicate that self-esteem also differentiates people who suffer EDs, not only from normal controls, but also from people who diet to lose weight (Gismero, 2001;Williams, 1993). Watson and Watts (2001) indicated that one's sense of personal value is based on the similarity between the perception of one's "present self" and "ideal self" in terms of the attributes important to the person. Based in Higgins's theory of selfdiscrepancies (1987), Strauman et al (1991) studied the relevance of the self-discrepancy in relation to body dissatisfaction and dysfunctional eating behaviours in college students, finding the discrepancy between the two self-images to be correlated to body dissatisfaction (independently of the participants' body mass index (BMI) and the number of beliefs about the self related to appearance).…”
Section: Self Construction Cognitive Conflicts and Disordered Eatingmentioning
confidence: 99%
“…This variable, identical to the self and ideal-self discrepancy measure of RGT, is considered to be an indicator of self-esteem (Arnold, 1988;Dada, Feixas, Compañ, & Montesano, 2012;Watson & Watts, 2001). Although the relation between this variable and the QCR has yet to be proven, Murstein (1971) and Solomon (1986) found that partners tend to be similar in their levels of self-esteem.…”
Section: Methodsmentioning
confidence: 99%